2018
DOI: 10.1104/pp.18.00107
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Mobile mRNAs to Plasmodesmata for Cell-to-Cell Movement

Abstract: 3 Abstract 30Many plant mRNAs move from cell to cell or long-distance to execute a 31 non-cell-autonomous functions. These mobile mRNAs traffic through the phloem to 32 regulate many developmental processes, but despite the burgeoning discovery of mobile 33 mRNAs, little is known about the mechanism underlying the intracellular sorting of these 34 mRNAs. Here, we exploited a fluorescence-based mRNA labeling system, using the 35 bacteriophage coat protein MS2, fused to GFP (MS2-GFP) and an MS2 recognition site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 43 publications
4
62
0
Order By: Relevance
“…Fluorescence-based mRNA-labeling systems combined with high-resolution confocal microscopy allows for visualizing the real-time trafficking of target mRNAs in live cells. Methods such as the GFP-MS2 RNA-tracking system (Hamada et al, 2003a;Luo et al, 2018) and its alternative approaches, including the boxB RNA stem-loop (Urbinati and Long, 2011), bacteriophage PP7 aptamer tagging (Wu et al, 2012), and spinach (Spinacia oleracea) tracking systems (Paige et al, 2011;Bann and Parent, 2012;Dean and Palmer, 2014;Tian and Okita, 2014), in combination with fluorescence resonance energy transfer and split-fluorescence protein systems (Ibragimov et al, 2014;Rath and Rentmeister, 2015;Mannack et al, 2016), can be utilized to simultaneously monitor the movement of different species of mRNAs along the cytoskeleton (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence-based mRNA-labeling systems combined with high-resolution confocal microscopy allows for visualizing the real-time trafficking of target mRNAs in live cells. Methods such as the GFP-MS2 RNA-tracking system (Hamada et al, 2003a;Luo et al, 2018) and its alternative approaches, including the boxB RNA stem-loop (Urbinati and Long, 2011), bacteriophage PP7 aptamer tagging (Wu et al, 2012), and spinach (Spinacia oleracea) tracking systems (Paige et al, 2011;Bann and Parent, 2012;Dean and Palmer, 2014;Tian and Okita, 2014), in combination with fluorescence resonance energy transfer and split-fluorescence protein systems (Ibragimov et al, 2014;Rath and Rentmeister, 2015;Mannack et al, 2016), can be utilized to simultaneously monitor the movement of different species of mRNAs along the cytoskeleton (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Free GFP was localized to the cytoplasm and the nucleus, as observed before. 20 We found that the AtNHR2B C-terminal deletion (AtNHR2B Δ141-342 - GFP) was localized to the cytoplasm only, suggesting that the localization to punctae requires the transmembrane domains ( Figure 4). The second truncated version (AtNHR2B Δ1-117, Δ223-342 -GFP) localized to the cytoplasm and to small dynamic punctae similar to the full-length protein, suggesting that the first transmembrane domain from amino acids 210 to 227 is sufficient to target the protein to punctae and, that this truncation represents the minimal protein size required for proper localization to cytoplasm and to subcellular endomembrane compartments just as the full length protein.…”
Section: Protein Domains In Atnhr2b Are Important For Protein Localizmentioning
confidence: 93%
“…It has been nearly a century since the initial demonstration that florigen functions as a mobile signal (Chaïlakhyan, ), and nearly two decades since its molecular characterization as FLOWERING LOCUS T (FT) (Takada & Goto, ; An et al ., ; Corbesier et al ., ; Jaeger & Wigge, ), and yet a complete understanding of the mechanisms for florigen function remain elusive. In addition to traveling as a protein signal (Corbesier et al ., ; Jaeger & Wigge, ; Mathieu et al ., ), there is a substantial body of evidence demonstrating that FT and related phosphatidylethanolamine‐binding protein (PEPB) family members move as transcripts, some of which exhibit selective intercellular trafficking (Li et al ., , ; Jackson & Hong, ; Lu et al ., ; Huang et al ., ; Luo et al ., ). Whether these mobile mRNAs serve as signals that contribute to the promotion of flowering is a long‐standing point of contention that has been challenging to resolve, because of the technical difficulty of separating the role of FT mRNA movement from the demonstrated function of FT protein in promoting reproductive transitions.…”
Section: Seasonal Changes In Developmentmentioning
confidence: 97%